Continuous Glucose Monitoring: A Transformative Approach to the Detection of Prediabetes - Liu X; Zhang J (Journal of Multidisciplinary Healthcare)
Xueen Liu,1 Jiale Zhang2 1Department of Nursing, Beijing Hepingli Hospital, Beijing, People’s Republic of China; 2Institute of Basic Theory for Chinese Medicine, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of ChinaCorrespondence: Jiale Zhang, Email zhang_tcm@163.comAbstract: Prediabetes, as an intermediary stage between normal glucose homeostasis and overt diabetes, affects an estimated 720 million individuals worldwide, highlighting the urgent need for proactive intervention strategies. Continuous glucose monitoring (CGM) emerges as a transformative tool, offering unprecedented insights into glycemic dynamics and facilitating tailored therapeutic interventions. This perspective scores the clinical significance of even slightly elevated fasting blood glucose levels and the critical role of early intervention. CGM technology provides real-time, continuous data on glucose concentrations, surpassing the constraints of conventional monitoring methods. Both retrospectively analyzed and real-time CGM systems offer valuable tools for glycemic management, each with unique strengths. The integration of CGM into routine care can detect early indicators of type 2 diabetes, inform the development of personalized intervention strategies, and foster patient engagement and empowerment. Despite challenges such as cost and the need for effective utilization through training and education, CGM’s potential to revolutionize prediabetes management is evident. Future research should focus on refining CGM algorithms, exploring personalized intervention strategies, and leveraging wearable technology and artificial intelligence advancements to optimize glycemic control and patient well-being.Keywords: continuous glucose monitoring, prediabetes, glycemic control, diabetes prevention strategies, transformative approach